A Study on Fraud Prevention in the Principles of Fiqh Dar'ul Mafasid - Setiawan, Nanang (Islamic Micro Finance Journal, 2024)
This paper aims to conduct an in-depth investigation of fraud prevention based on the principles of fiqh dar'ul mafasid. This research employs a qualitative literature review approach, drawing from books, scholarly journals, and other sources related to fiqh muamalah and fraud. The study is grounded in Islamic fiqh muamalah, which posits that preventing harm (mafsadah) is more crucial than obtaining benefits. Mafsadah encompasses all damages resulting from violations, and fraud is one form of mafsadah that must be prevented. Preventing fraud and complying with Islamic law's commands to avoid prohibitions also significantly impact the prioritization of preventing potential damage risks, both financially (maaliyah) and non-financially. This research enhances literacy and expands scientific insights regarding the fiqh muamalah review in Islamic law concerning fraud phenomena and its prevention programs.